A decade of crisis in black education, 1976-1986 - Marambana, Nomaswazi Rosamond (My University, 1987)
Refer to the document
Thesis (M.A. (Education)) -- University of the North, 1987
Keywords: Discrimination; Black education; 1976 riots; Educational sociology; School violence; Discrimination in education